1998
DOI: 10.1021/jf980276e
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition in Developing High Saturated Sunflower (Helianthus annuus) Seeds:  Maturation Changes and Temperature Effect

Abstract: Developing seeds from sunflower high palmitic acid mutants showed high levels of palmitic acid at early stages. The stearic acid content of high stearic mutants (CAS-3, CAS-4, and CAS-8) increased from low or medium initial values until it reached the maximum level at 16 days after flowering. All mutant lines increased palmitic acid content at high growth temperature with CAS-5 having the maximum increase (5.7%). At the same time, all but CAS-3 increased stearic acid content at low temperature with CAS-8 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
8
20
0
Order By: Relevance
“…Also, in the medium stearic acid mutants CAS-4 and CAS-8, an inverse relationship between growth temperature and stearic acid proportions was reported. At 30/20°C day/night temperature, these mutants had 11-12% stearic acid, whereas at 20/10°C, they contained 18-20% stearic acid (Martínez-Force et al 1998). In another study by Izquierdo et al (2013) with the CAS-3 mutant, the stearic acid content at 16/16°C was higher than at 26/26°C (26.2 vs. 18.4%) during the grain filling period.…”
Section: Drought and High Temperaturesmentioning
confidence: 91%
“…Also, in the medium stearic acid mutants CAS-4 and CAS-8, an inverse relationship between growth temperature and stearic acid proportions was reported. At 30/20°C day/night temperature, these mutants had 11-12% stearic acid, whereas at 20/10°C, they contained 18-20% stearic acid (Martínez-Force et al 1998). In another study by Izquierdo et al (2013) with the CAS-3 mutant, the stearic acid content at 16/16°C was higher than at 26/26°C (26.2 vs. 18.4%) during the grain filling period.…”
Section: Drought and High Temperaturesmentioning
confidence: 91%
“…Robertson et al (1978) found during seed development, that for each 1ºC decrease in temperature, oleic acid decreased by 0.87% and linoleic acid increased by 0.32%. Martínez-Force et al (1998) investigated the changes in fatty acid composition during maturation and the effects of temperature on normal fatty acid content in developing sunflower seeds. At 35 DAF, the linoleic/oleic acid ratio was lower in the seeds under the high-temperature condition (30/20ºC day/night) than that under the lowtemperature condition (20/10ºC day/night).…”
Section: Discussionmentioning
confidence: 99%
“…The changes of seed oil percentage, fatty acid compositions and dry weight with seed maturation (Robertson et al, 1978) and the changes in fatty acid compositions and the effects of temperature condition (Martínez-Force et al, 1998) have been analyzed. Baydar and Erbaş (2005) tracked changes in the quality of linoleic hybrid seeds and found that the oil content increased, oleic acid content decreased, and linoleic acid content increased during the seed maturation process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent programs of sunflower improvement have produced a second generation of modified sunflower oils in which their fatty acid composition differed much more from that in regular sunflower (Table 1). These mutants display high levels of saturated fatty acids, displaying very different physical properties and having a high potential for industrial applications [17,18]. The compositions of some of them are depicted in Table 1, where typical compositions of high stearic and high palmitic sunflower mutants are shown.…”
Section: Sunflower Mutant Linesmentioning
confidence: 99%